Economic Burden of Reported Lyme Disease in High-Incidence Areas, United States, 2014–2016 - Sarah A. Hook; Seonghye Jeon; Sara A. Niesobecki; AmberJean P. Hansen; James I. Meek; Jenna K.H. Bjork; Franny M. Dorr; Heather J. Rutz; Katherine A. Feldman; Jennifer L. White; P. Bryon Backenson; Manjunath B. Shankar; et al. (Emerging Infectious Diseases, 2022)
Approximately 476,000 cases of Lyme disease are diagnosed in the United States annually, yet comprehensive economic evaluations are lacking. In a prospective study among reported cases in Lyme disease–endemic states, we estimated the total patient cost and total societal cost of the disease. In addition, we evaluated disease and demographic factors associated with total societal cost. Participants had a mean patient cost of ≈$1,200 (median $240) and a mean societal cost of ≈$2,000 (median $700). Patients with confirmed disseminated disease or probable disease had approximately double the societal cost of those with confirmed localized disease. The annual, aggregate cost of diagnosed Lyme disease could be $345–968 million (2016 US dollars) to US society. Our findings emphasize the importance of effective prevention and early diagnosis to reduce illness and associated costs. These results can be used in cost-effectiveness analyses of current and future prevention methods, such as a vaccine.